2018
DOI: 10.1007/s00167-018-4993-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone bruise in anterior cruciate ligament rupture entails a more severe joint damage affecting joint degenerative progression

Abstract: Purpose During anterior cruciate ligament (ACL) injury, the large external forces responsible for ligament rupture cause a violent impact between tibial and femoral articular cartilage, which is transferred to bone resulting in bone bruise detectable at MRI. Several aspects remain controversial and await evidence on how this MRI finding should be managed while addressing the ligament lesion. Thus, the aim of the present review was to document the evidence of all available literature on the role of bone bruise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 99 publications
4
61
0
1
Order By: Relevance
“…An important finding of this study was that pediatric and adult patients display similar bone bruise localization, 22 which is in contrast with previous evidence showing that patients with open physes at the occurrence of an acute ACL rupture have unique bone bruise patterns compared with those with closed physes. 29 As reported in the Results section, the lateral central femur and the lateral posterior tibia were the areas most commonly affected by bone bruises in the pediatric patients included in this study; as reported by Filardo et al, 6 these are also the areas most commonly affected by bone bruises in adults. This finding indicates that the mechanisms that lead to ACL tears are the same regardless of age.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…An important finding of this study was that pediatric and adult patients display similar bone bruise localization, 22 which is in contrast with previous evidence showing that patients with open physes at the occurrence of an acute ACL rupture have unique bone bruise patterns compared with those with closed physes. 29 As reported in the Results section, the lateral central femur and the lateral posterior tibia were the areas most commonly affected by bone bruises in the pediatric patients included in this study; as reported by Filardo et al, 6 these are also the areas most commonly affected by bone bruises in adults. This finding indicates that the mechanisms that lead to ACL tears are the same regardless of age.…”
Section: Discussionsupporting
confidence: 74%
“…In the pediatric patients analyzed in this study, the prevalence of bone bruises (69%) seemed to be slightly lower than in adults. 6,29 In fact, although high prevalence values have been reported in the overall literature, the most recent findings (excluding older studies with poor imaging techniques) documented a 78% prevalence. 6 It is possible that the higher ligamentous laxity of younger patients, along with differences in their tissue composition, reduces the trauma that follows an ACL lesion, thus leading to a lower incidence of bone bruise than in adults.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations